Minat Belajar Anggota Serikat Pekerja Nasional dalam Meningkatkan Kinerja dan Kualitas Diri (Studi Kasus Mahasiswa Kelas Malam SPN di Universitas Bina Bangsa Bangsa) - Masriyadi Masriyadi; Eka Isnarini; Yunika Br. Naibaho; Juwita Sari; April Laksana (Journal on Education, 2023)
The impact that occurs in the field shows a decrease in the learning spirit of students. Not only in the education sector, all the impacts of Covid-19 have many obstacles and factors that workers face in order to learn, but the motivation of workers in the industry to continue their education is disrupted due to factors that indeed limit their mobility to learn. Workers increase their skills as individuals to gain self-quality by participating in training, formal and informal education. Worker's capacity is valued by the company from the potential development that the worker has to receive a fair welfare from the company in terms of allowances, bonuses, and performance evaluations achieved by the worker. The purpose of this research is for the researcher to understand the motivation of members of the National Workers' Union to learn, the factors that affect the motivation of workers to become night class students, to understand how the learning motivation of night class students affects their performance and self-quality. This research uses descriptive qualitative research methodology by conducting interviews with members of the SPN as night class students at Bina Bangsa University who are workers. Interest in learning is one of the motivations that is needed for workers, as one factor for career development for workers in improving their performance and self-quality.